2021
DOI: 10.1556/2006.2021.00035
|View full text |Cite
|
Sign up to set email alerts
|

Prosocialness in young males with substance and behavioral addictions

Abstract: Background and aimsSocial determinants are closely related to addiction, both as a cause and a consequence of substance use and other addictive behaviors. The present paper examines prosocialness (i.e. the tendency to help, empathize, and care for others) among a population of young males. We compared prosocialness across different types of addiction and examined whether prosocialness varied according to the presence of multiple addictions.MethodsA sample of 5,675 young males, aged 19–29 years old (Mean = 21.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 76 publications
(88 reference statements)
0
4
0
Order By: Relevance
“…In the case of the relationship between cannabis use and prosocial behaviours, 10.34% ( n = 3) of the results show that both variables are negatively related, while 3.44% ( n = 1) reflected a positive relationship, and another 3.44% ( n = 1) found no significant differences [ 50 ]. In particular, the results showed that prosocial behaviour during adolescence acts as a protective factor against problematic cannabis consumption in adulthood [ 25 ] and that cannabis users showed less prosocial behaviour in adulthood [ 23 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the case of the relationship between cannabis use and prosocial behaviours, 10.34% ( n = 3) of the results show that both variables are negatively related, while 3.44% ( n = 1) reflected a positive relationship, and another 3.44% ( n = 1) found no significant differences [ 50 ]. In particular, the results showed that prosocial behaviour during adolescence acts as a protective factor against problematic cannabis consumption in adulthood [ 25 ] and that cannabis users showed less prosocial behaviour in adulthood [ 23 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…The psychological literature provides a wealth of information about various individual characteristics that may be associated with developing problematic gambling [75,76,[143][144][145][146][147][148][149][150][151][152][153][154][155][156], and how these may be experienced across various life stages and related to other risky behaviours [98,[157][158][159][160][161][162][163]. The interaction of comorbid mental health issues has been clearly associated with gambling-related harm [164,165], with a strong relationship between depression, anxiety and at-risk or problem gambling.…”
Section: Overviewmentioning
confidence: 99%
“…Active participation in these groups allows patients to develop lasting friendships and find a supportive community that can help them navigate challenges and maintain their recovery. The camaraderie and shared experiences in these groups can promote a sense of belonging and reduce feelings of isolation, which are often struggles for individuals with addictive disorders ( Estévez et al, 2017 ; Dingle et al, 2018 ; Tomei et al, 2021 ).…”
Section: Schema Therapy: What It Has To Offermentioning
confidence: 99%
“…As these children become adolescents, they often gain access to even more expedient and/or effective avoidance strategies, such as illicit substances, masturbation, shopping, and gaming ( Burkett and Young, 2012 ). Indeed, some addictive behaviors, particularly behavioral addictions, appear at startlingly young ages ( Kuss and Griffiths, 2012 ; Tomei et al, 2021 ). Although there is ongoing debate over classifying Compulsive Sexual Behavior Disorder (ICD-11) as a behavioral addiction ( Kraus et al, 2016 ; Sassover and Weinstein, 2022 ), for the purposes of this discussion, these behaviors are characterized as addictive due to shared criteria and the functioning of coping modes.…”
Section: Introductionmentioning
confidence: 99%